2012
DOI: 10.1145/2325722.2325725
|View full text |Cite
|
Sign up to set email alerts
|

Single-trial EEG classification of artifacts in videos

Abstract: In this article we use an ElectroEncephaloGraph (EEG) to explore the perception of artifacts that typically appear during rendering and determine the perceptual quality of a sequence of images. Although there is an emerging interest in using an EEG for image quality assessment, one of the main impediments to the use of an EEG is the very low Signal-to-Noise Ratio (SNR) which makes it exceedingly difficult to distinguish neural responses from noise. Traditionally, event-related potentials have been used for ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
34
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(34 citation statements)
references
References 26 publications
0
34
0
Order By: Relevance
“…); this is similar to what is done with listening quality assessment of text-to-speech systems. As in previous literature, we have shown that EEG can be used to gather cognitive, distortion, and quality-of-experience insights ( [6], [8], [9], [16]). …”
Section: Discussionmentioning
confidence: 54%
See 1 more Smart Citation
“…); this is similar to what is done with listening quality assessment of text-to-speech systems. As in previous literature, we have shown that EEG can be used to gather cognitive, distortion, and quality-of-experience insights ( [6], [8], [9], [16]). …”
Section: Discussionmentioning
confidence: 54%
“…For example, [6] showed that simple degradations in the speech signal (e.g., multiplicative noise) could be processed by humans at an unconscious level; similar findings were also observed for artificial audiovisual stimuli [7]. Recently, P300 peak amplitudes were shown to be significantly correlated with the level of distortions added to audiovisual stimuli [8] and classifiers were developed to discriminate between clean and distorted visual stimuli based only on EEG [9]. Lastly, EEG has also been used to characterize user emotional state while watching Youtube videos [10].…”
Section: Introductionmentioning
confidence: 83%
“…However, those measures did not show any significant change with the change of quality [28]. Mustafa et al [13] used a 5.6 s long low-complexity video that showed a person walking. They introduced different kinds of distortion, such as partial freezing and blurring (on the person, and on a greater area), ghosting of the movement plus the original video, resulting into six different video conditions.…”
Section: Spectral Analysismentioning
confidence: 99%
“…2. Using classification techniques this can be transferred to online analysis of incoming physiological signals, such as deciding whether the brain activity of the proceeding stimulus was evoked by one special class of stimuli [13]. To address this in the case of Quality of Experience an exemplary class of degradation can be used.…”
Section: Neurophysiologymentioning
confidence: 99%
See 1 more Smart Citation